Middle-term loss prediction models for the Air Force's enlisted force management system : specification and estimation - Carter, Grace M.; Drezner, Deborah S. (Deborah Skoller), 1956-; Greenberg, Harvey J.; Abrahamse, Allan F.; Brauner, Marygail K., 1947-; Arguden, R. Ylmaz; Murray, Michael P., 1946-; Rand eBooks (Santa Monica, CA : RAND, 1987)
This study specifies equations for models that predict the loss and reenlistment behavior of airmen. The cohort models described here--where cohorts are defined based on an airman's position in his career--provide information about how airmen would respond to changes in economic conditions, military pay raises, and bonuses. Developed for the Air Force's Enlisted Force Management System, these models allow forecasts of the behavior of different demographic groups and people in different occupations.
"December 1987."
"Project Air Force"--Cover.
Includes bibliographical references (p. 83).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States. -- Air Force -- Personnel management -- Mathematical models; Electronic books